KINERJA KEUANGAN PERBANKAN DENGAN PENDEKATAN RISK-BASED BANK RATING - Isfandayani, Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
Shari?a Mandiri Bank and Bukopin Bank finances have a less significant difference when viewed from total assets at the end of 2014, which is only a difference of 12.109 trillion rupiah. It indicates that both have a performance that is not much different. This study aims to determine the differences in financial performance between Shari?a Mandiri Bank and Bukopin Bank during 2010-2014 by using Risk-based Bank Rating (RBBR) approach analysis. Risk-Based Bank Rating is a financial performance approach issued by the Financial Authority for banks in Indonesia in order to conduct self assessment on possible risks based on Bank Rating (composite rating). This research is included in quantitative research using a comparative approach that is, the researchers compare the financial performance of the two Banks. Results of research There are significant differences so that H1 is accepted while H0 is rejected because, the value of t arithmetic <0,05 is equal to 0,028. Evident from the composite rating in both Banks, Bukopin Bank has a very Healthy Composite Ranking of 90% when compared with Shari?a Mandiri Bank which is equal to 73% who has a Health rating.